Extreme Precipitation and Floods: Monitoring, Modelling, and Forecasting - Zheng, Duan; Hongkai , Gao; Mouleong , Tan (Hindawi Publishing Corporation, 2017)
Flooding is one of the leading natural hazards [1]. Floods often cause enormous casualties and substantial property damage on a global scale every year. Extreme precipitation alongwith increasing urbanization is the main culprit of most floods. Under climate change, increases in extreme precipitation are projected for the United States and other countries. Understanding themechanisms of extreme precipitation and its hydrometeorological connection with flooding, especially under the circumstances of global climate change, is essential for flood prevention and mitigation. Extreme precipitation and flood monitoring are traditionally obtained from in situ observations. However, remote sensing provides us with various hydrological and meteorological retrievals at a range of temporal and spatial resolutions. Remotely sensed data alone and their integration with modelling techniques are expected to enhance flood monitoring and modelling capability to aid in decision-making. There is an urgent need for improved monitoring, modelling, and forecasting techniques in extreme precipitation to develop more effective flood protection measures and management.